Education Promoted Secularization - Sascha O. Becker; Markus Nagler; Ludger Woessmann (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
Why did substantial parts of Europe abandon the institutionalized churches around 1900? Empirical studies using modern data mostly contradict the traditional view that education was a leading source of the seismic social phenomenon of secularization. We construct a unique panel dataset of advanced-school enrollment and Protestant church attendance in German cities between 1890 and 1930. Our cross-sectional estimates replicate a positive association. By contrast, in panel models where fixed effects account for time-invariant unobserved heterogeneity, education but not income or urbanization is negatively related to church attendance. In panel models with lagged explanatory variables, educational expansion precedes reduced church attendance.
Keywords: Z12; N33; I20; 330; secularization; education; history; Germany